DEVELOPMENT OF HOTS-BASED TEST INSTRUMENTS TO MEASURE STUDENTS' CRITICAL THINKING SKILLS MAJOR MATERIALS AND UNIT - Panuqih, Frisma Winda Afifah; Sabani, Sabani (UNIVERSITAS NEGERI MEDAN, 2024)
This study aims to develop a HOTS-based test instrument in measuring students' critical thinking skills on the material of quantities and units at SMAN 2 Rambah Hilir which has met the criteria for testing the instrument's feasibility including content validity, item validity, reliability testing, level of difficulty, discriminating power, and student response test. This research is a research development or Research and Development (RnD) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research was conducted at SMA Negeri 2 Rambah Hilir with the research subjects of class X MIPA SMA Negeri 2 Rambah Hilir. Based on the data obtained from content validity with the Lawshe technique, 10 questions were obtained that could be used. Meanwhile , from testing the validity of the items , there are 8 valid questions and 2 invalid questions . In the reliability test obtained a value of 0.543390 with moderate correlation criteria. For the level of difficulty, scores ranged from 0.297 to 0.70 with the criteria that 1 item was said to be easy, 1 item was said to be difficult, and 8 items were said to be moderate . While different power derive a value of -1 , 8 - 2.5 with a category 2 a matter of saying ugly and the two problems said to be good at all. Meanwhile, to test students' response was obtained by 78 , 1 % in both categories. The conclusion from the overall test results is that the HOTS-based test instrument is feasible to use to measure critical thinking skills.Keywords : Development of Test Instruments, Critical Thinking Skills, Quantities and Units